Visualization Experiment Study on Heat Transfer Characteristic and Limit of High-temperature Oscillating Heat Pipe - YANG Xin, JI Yulong (Yuanzineng kexue jishu)
The high-temperature oscillating heat pipe (HTOHP) has broad application prospects in the field of high heat flux dissipation in high-temperature environments such as nuclear energy and aerospace because of its efficient heat transfer capability and simple structure. To conduct an in-depth analysis of the heat transfer characteristics and heat transfer limit of the HTOHP, a visualization experiment setup was constructed. By utilizing X-ray imaging technology, the working and heat transfer limit states of a single-turn HTOHP with cesium as the working fluid were visualized. Additionally, an analysis of the wall temperature field was conducted to explore the thermal performance changes and flow state transitions of the HTOHP as the heating power increased. The results indicate that the thermal resistance decreases from 1.62 ℃/W at 250 W to 0.84 ℃/W at 400 W, and rapidly increases after reaching the heat transfer limit at 450 W. This phenomenon is primarily due to the transition of the working fluid from an oscillating flow state to unidirectional flow state as the heating power increases. When reaching the heat transfer limit, the working fluid stopovers and then accumulates in the condensation section of the HTOHP, preventing return flow, although a liquid film still flows down along the tube wall. When the HTOHP starts up and at a low heating power of 250 W, a phenomenon is observed where the unidirectional flow state cannot be sustained. This is because under low heating power conditions, after entering unidirectional circulation, the heat transfer efficiency of the HTOHP is improved, causing a decrease in the temperature of the evaporation section. This results in a reduced phase change heat transfer rate, which is insufficient to maintain unidirectional flow. At the limit power, due to the working fluid of the HTOHP being in unidirectional flow and unable to form a more optimal flow state, the heat from the evaporation section cannot be fully dissipated, leading to a continuous increase in the evaporator section temperature. When the evaporator section temperature reaches 656.71 ℃, due to the excessive rate of evaporative heat transfer, a stopover phenomenon occurs under the influence of working fluid pressure, ultimately resulting in the heat transfer limit being reached. It is worth noting that at the heat transfer limit state, there is still a liquid film adhering to the wall and flowing downward. Consequently, the adiabatic and evaporation sections of the HTOHP are not filled with gas. Therefore, the limit state does not exist in a manner where the pipe conducts heat solely as an empty tube.